ANALISIS YURIDIS TERHADAP KEKUATAN PEMBUKTIAN AUDIT INVESTIGASI OLEH BADAN PENGAWASAN KEUANGAN DAN PEMBANGUNAN SEBAGAI KETERANGAN AHLI DALAM PENANGANAN TINDAK PIDANA KORUPSI - WAHYUDI, PANDJY SATRIA; Kusuma, Zulfikar Jaya; Erdiansyah, Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Indonesia is a state based on law. One of the legal rules used in a criminalprocedure, namely the criminal procedure code as a codification and legalunification. Based on the provisions of Article 184 paragraph (1) of the Law onCriminal Procedure (Criminal Procedure Law) states about legal evidence, oneof which is expert statements. In the provisions of article 1 number 28 of thecriminal procedure code it is regulated about expert statements as legal evidenceaccording to law. Disclosure of corruption through witness testimony from anexpert in the financial and development oversight body is very influential andstrengthens the confidence of the judge in considering strong and valid evidencebefore the trial. The purpose of this is: first, to find out the form of evidence of thestrength of the investigative audit by the Financial and Development SupervisoryAgency as an expert statement in handling corruption. Second, to find out thebasis for conducting an audit investigation by the Financial and DevelopmentSupervisory Agency as an expert statement in handling corruption.This research is a normative juridical. The data source is secondary dataconsisting of primary legal materials, secondary law and tertiary legal materials.Data collection techniques in this study is a review of literature and documentarystudies and data analysis use thecnical deductive method.From the results of the study it can be concluded, first, the form of thestrength of the evidence of an investigative audit by the Financial andDevelopment Supervisory Agency as an expert statement in the handling ofcriminal acts of corruption is divided into several forms, namely physical testing,confirmation evidence, documentary evidence, observational evidence, questionand answer evidence by auditing, re-implementation, and analysis procedures.Second, the basis of the strength of the evidence of investigative audit by theFinancial and Development Supervisory Agency as an expert statement inhandling corruption is as a fulfillment of the request letter from the investigatingagency or the public prosecutor in accordance with the Decision of theConstitutional Court Number 31 / PUU-X / 2012 October 23, 2012.Keyword: Corruption Crime-Investigative Audit-Expert Statement